Analyzing the communicative practices of Yambo lake livelihood association’s batak boys in reducing role uncertainty of the new volunteers - Cuevas, Patricia Nicole M. (Animo Repository, 2023)
This research is about role uncertainty as an organizational communication issue. It looks at the case of the new volunteer member Batak Boys, a volunteer group in Yambo Lake Livelihood Association in Nagcarlan, Laguna, Philippines. Guided by Uncertainty Reduction Theory (URT) (Kramer, 1994), the study identifies the new Batak Boys’ sources of role uncertainty in the organization. It also looks at the communicative practices utilized by their group of trainers, the senior Batak Boys, to evaluate its appropriateness in reducing the said role uncertainty. The proponents facilitated 17 in-depth semi-structured interviews with the new and senior Batak Boys, and Livelihood Association members and one-month participant observation. The data revealed that the new Batak Boys’ key uncertainty sources came from unfamiliarity and newness in the organization, the volume of workload, and the assumption of the senior Batak Boys that new members do not need re-orientation about their roles. Moreover, the communicative practices utilized by senior Batak Boys—weekly alignment meetings, onsite training, and group chat announcements—did reduce uncertainty among the newcomers. There were still gaps, however, in further eradicating role uncertainty, specifically with additional and emerging unmapped roles. The results affirmed the claims of URT that better alignment of new volunteers’ collective understanding of job roles and expectations is rooted in effective communicative practices of the organization to prevent role uncertainty. Based on the data, the proponents came up with organizational communicative interventions to improve the communication practices of senior Batak Boys.